TALABALARDA MA'NAVIY-AXLOQIY KOMPETENSIYANI RIVOJLANTIRISHDA INTERFAOL METODLAR VA ZAMONAVIY AXBOROT TEXNOLOGIYALARINING AHAMIYATI - Muxambaev Temur Saparbaevich (International Journal of Literature and Language Studies, 2026)
This article provides a scientific and theoretical analysis of the role and significance of interactive methods and modern information technologies in developing students’ spiritual and moral competence. The study examines the competency-based approach, the methodology of interactive learning, and issues related to moral development in the digital environment. Based on the scientific works of Uzbek and foreign scholars, pedagogical experience is generalized and practical recommendations are developed.